Comparative Study on the Test Method for Tensile Elastic Modulus of Rock Materials - Yan Zhang; Dawei Yu (Advances in Civil Engineering)
Rock material has different mechanical behaviors under compressive and tensile loading. Correspondingly, there are two types of elastic modulus: compressive elastic modulus Ec and tensile elastic modulus Et, respectively. To distinguish which indirect test methodology, including three-points bending test and Brazilian disc test, is more suitable to measure the tensile elastic modulus Et of rock materials, a series of uniaxial compressive test (UCT), direct tensile test (DTT), three-points bending test, and Brazilian disc test are performed for three typical types of rock: marble, granite, and sandstone. Comparative investigation on the reliability of measurement results of tensile elastic modulus Et is systematically conducted. Finally, it is found that Brazilian disc test could be a suitable method to measure tensile elastic modulus of rock materials, due to the excellent agreement with that measured by DTT and the simplicity of sample preparation, as well as test operation.